Analisis Sinergi Pokdarwis Desa Gondosuli dan Perhutani dalam Pengelolaan Wisata Bukit Mongkrang Karanganyar Jawa Tengah - Nabila Saroja Estiyantara (Altasia Jurnal Pariwisata Indonesia, 2022)
Indonesian tourism is a leading sector that can significantly increase revenue for the country and the region. The regional tourism development process is also based on the Regional Tourism Development Master Plan. This did not escape the interfering role of the local Pokdarwis in the development of the regional tourism sector. So far, there is still a lot of potential for the tourism sector in the area that is no less interesting than the central tourism sector, one of which is the Bukit Mongkrang Tourism Destination located in Gondosuli Village, Tawangmangu District, Karanganyar Regency, Central Java which is a tourist destination resulting from the synergy between Pokdarwis with Perhutani (BUMN). Pokdarwis plays an important role in the management of Mongkrang Hill tourism. The purpose of holding this research is to find out the synergies and profit-sharing cooperation systems carried out by Perhutani and Pokdarwis in the management of Mongkrang Hill Tourism. In addition, this study aims to describe what roles Pokdarwis plays in managing Mongkrang Hill tourism and the perceived impact and what factors support and hinder the development process of Mongkrang Hill Tourism Destinations. The author uses a descriptive research method with a qualitative approach in this study. With data collection techniques obtained from in-depth interviews and field observations as primary data sources, as well as related journals and other scientific articles used as secondary sources. Data analysis was obtained in the form of a clear picture of the object of research and conclusions were drawn. The results showed that the synergy between Perhutani and Pokdarwis went smoothly, supported by the role of Pokdarwis in object management and the utilization of Mongkrang Hill Tourism potential was quite good.